(untitled) (Swiss Medical Weekly, 2015)
Infections of cardiovascular implantable electric devices (CIED) are a burden on patients and healthcare systems and should be prevented. The most frequent pathogens are coagulase-negative staphylococci and Staphylococcus aureus. The most important risk factors for CIED infections are diabetes mellitus, renal and heart failure, corticosteroid use, oral anticoagulation, fever within 24 hours before the procedure and leucocytosis, implantable cardioverter defibrillator compared with pacemaker, especially in the case of Staphylococcus aureus bacteraemia, lack of antibiotic prophylaxis, and postoperative haematoma and other wound complications. Other important risk factors are history of prior procedures and previous CIED infections, number of leads, use of povidone-iodine compared with chlorhexidine-alcohol, and centres and operators with a low volume of implants. To prevent CIED infections, patients undergoing CIED procedures and appropriate devices should be carefully selected, and interventions should be performed by trained operators. Antibiotic prophylaxis should be administered, and skin antisepsis should be done with chlorhexidine-alcohol. Oral anticoagulation should be continued during CIED procedures in high-risk patients for thromboembolism, instead of bridging with heparin. Early reintervention in cases of haematoma or lead dislodgement should be avoided. The implementation of infection prevention programmes reduces infection rates. More randomised controlled studies are needed to evaluate prevention strategies, especially skin preparation and antibiotic prophylaxis with glycopeptides.